SISTEM MANAJEMEN STRATEGI DALAM PENGUKURAN KINERJA PERUSAHAAN - PAWER D PANJAITAN (JURNAL ILMIAH KOHESI, 2021)
Nowadays, the companies are in the middle of the information competition century. To achieve competitivesuccess, the century information environment requires the new ability of the companies must be owned by themanufacturing and services. A company's ability to process information from a variety of instruments is absolutelyneed, steer the company to across the complex competitive environment. Company requires instrument which capable ofexplaining various aspects of the environment and performance in monitoring of travel towards a promising future.Balanced Scorecard provides an instrument that is required to steer the company toward the future success of thecompetition. An accurate understanding about the goals and methods for achieving it is very vital. Balanced Scorecardtranslates mission and strategy of the company in to a comprehensive measure that provides a framework formeasurement and strategic management system. Scorecard measures the performance of companies on the fourperspectives of balanced: financial, customer. internal business processes, and learning growth. Balanced Scorecardenables companies to record financial performance results as well as monitor progress in building the company's abilityand to obtain intangible assets that required for future growth.